2017
DOI: 10.1155/2017/4716245
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Paravertebral Mass as an Infrequent Manifestation of IgG4-Related Disease

Abstract: Case A 50-year-old African American male presented with abdominal pain and significant weight loss. On physical examination, he had parotid and submandibular gland enlargement associated with right eye proptosis. Computed tomography showed a thoracic paravertebral soft tissue mass, enlarged lymph nodes, and ascending aortic aneurysm. Laboratory results were remarkable for elevated total IgG and IgG4 subclass. The submandibular gland pathology revealed chronic sclerosing sialadenitis, with a large subset of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Similarly, a small amount of salivary tissue frequently occurs in intra‐ or peri‐parotid cervical lymph nodes, which may justify the existence of lymphadenopathy in patients with IgG4‐RS. In addition to lymphadenopathy, the simultaneous occurrence of other circulatory system involvements such as pericarditis, Morita et al, 2014 occlusive vasculitis, Ikeoka et al, 2019 and ascending aortic aneurysmMatzumura Kuan et al, 2017 has also been reported among patients with IgG4‐RS. Dental clinicians should pay extra attention to these potentially fatal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a small amount of salivary tissue frequently occurs in intra‐ or peri‐parotid cervical lymph nodes, which may justify the existence of lymphadenopathy in patients with IgG4‐RS. In addition to lymphadenopathy, the simultaneous occurrence of other circulatory system involvements such as pericarditis, Morita et al, 2014 occlusive vasculitis, Ikeoka et al, 2019 and ascending aortic aneurysmMatzumura Kuan et al, 2017 has also been reported among patients with IgG4‐RS. Dental clinicians should pay extra attention to these potentially fatal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The three share a newly described gene variant in fibroblast growth factor binding protein 2 ( FGFBP2 ), OMIM: 607713, and markedly elevated blood plasmablasts and CD4 + cytotoxic T cells. Heritable IgG4‐RD has been inferred in prior reports, but no information exists on genetic features that may predispose to disease (Comings, Skubi, Van Eyes, & Motulsky, ; Matzumura, Rubin, & Meysami, ).…”
Section: Introductionmentioning
confidence: 99%